Basics of single leg jumping - Bosch, F. (IFAC, 2013)
The discussed points of interest are: • elasticity versus power, • muscle slack as influential factor for performance, • using reflexes in take off, • amortization in power and speed jump, • p-step, • preparing for p-step, • regulating stride-length.